Battery cell, battery device, and electric device, method for manufacturing battery cell

CN122800614APending Publication Date: 2026-09-22CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510326748.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2026-09-22

AI Technical Summary

Benefits of technology

[0029]由此,本公开粘结剂前体在聚酰胺酸类化合物芳香环侧链引入上述吸电子基团,上述吸电子基团与芳香环直接相连,可以降低苯环上电子云密度,降低C-N键成键的活化能,促进亚胺化反应,使聚酰胺酸在较低的温度下可以环化,降低交联固化的温度,如在将浆料涂覆在集流体上后,可以在烘干的过程中(120℃)完成交联固化,减少了设备投入成本和能耗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122800614A_ABST
    Figure CN122800614A_ABST
Patent Text Reader

Abstract

The present disclosure discloses a battery monomer, a battery device, and a power utilization device, and a preparation method of the battery monomer. A battery monomer provided by an embodiment of the present disclosure comprises a negative electrode sheet, the negative electrode sheet comprises a current collector and a negative electrode active material layer which are arranged in a stack, and the negative electrode active material layer comprises a binder. The benzene ring and the imide structure in the binder have good mechanical strength and tensile strength. On this basis, an electron-withdrawing group is introduced into the aromatic ring side chain, the interfacial bonding force between the binder and the silicon-based material is enhanced, the integrity of the silicon is maintained when the volume of the silicon expands, the negative electrode active material layer is not prone to falling off or pulverization, the structural stability of the negative electrode active material layer is strengthened, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of batteries, and in particular to a battery cell, a battery device, an electrical device, and a method for preparing the battery cell. Background Technology

[0002] Battery cells possess characteristics such as high capacity and long lifespan, making them widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric cars, electric airplanes, electric ships, electric toy cars, electric toy ships, electric toy airplanes, and power tools. Due to significant advancements in battery cell technology, higher demands are now placed on their cycle performance. Summary of the Invention

[0003] This disclosure provides a battery cell, a battery device, an electrical device, and a method for preparing a battery cell, which can improve the cycle performance of the battery cell.

[0004] In a first aspect, the present disclosure provides a battery cell including a negative electrode sheet, the negative electrode sheet including a current collector and a negative electrode active material layer stacked together, the negative electrode active material layer including a binder, the binder including a compound having the structure shown in formula (I);

[0005]

[0006] Each of R1 to R8 independently represents at least one of hydrogen atom, nitro, cyano, sulfonic acid group, fluoroalkyl group, carboxyl group, acyl group, and formyl group; at least one of R1 to R8 includes one of nitro, cyano, sulfonic acid group, fluoroalkyl group, carboxyl group, acyl group, and formyl group.

[0007] The benzene ring and imide structure in the binder possesses excellent mechanical and tensile strength. Introducing electron-withdrawing groups, such as those mentioned above, directly into the aromatic ring side chains can enhance the interfacial bonding between the binder and the negative electrode active material, such as silicon-based materials. For example, nitro groups can enhance the adhesion between the binder and the negative electrode, suppressing the volume expansion of silicon during cycling. Cyano-containing polymers have better elasticity, increasing the mechanical flexibility of the electrode and thus adapting to changes in the negative electrode volume. The high polarity and strong hydrogen bonding of sulfonic acid groups can improve the adhesion between the binder and the negative electrode active material, effectively suppressing volume expansion during charge and discharge, reducing crack formation, and extending cycle life. Carboxyl groups are coordinated with the surface of the negative electrode active material, exhibiting good adaptability to volume changes. Acyl groups can form a cross-linked network through condensation reactions, enhancing the mechanical strength of the binder and suppressing the volume expansion of the negative electrode active material. Therefore, the structural stability of the negative electrode active material layer is strengthened, improving the battery's cycle performance.

[0008] In some embodiments, R1 and R3 each independently include at least one of sulfonic acid group, fluoroalkyl group, nitro group, and cyano group.

[0009] In some embodiments, R1 and R3 are each independently selected from at least one of sulfonic acid group, fluoroalkyl group, nitro group, and cyano group.

[0010] Therefore, R1 and R3, each consisting of the aforementioned groups directly connected to the benzene ring and concentrated on one side, enable the binder to form a more directional and selective interaction with the silicon material surface. This facilitates a more ordered arrangement of the binder molecular chains on the silicon material surface, resulting in a denser and more regular adhesive layer, further enhancing the bonding effect and strengthening the stability of the electrode structure. On the other hand, sulfonic acid groups, in addition to being electron-withdrawing groups that can dissociate protons, can also promote lithium-ion conduction, thereby improving the conductivity of the binder and ultimately improving the kinetic performance of the electrode.

[0011] In some embodiments, R2 and R4 each independently include at least one of hydrogen atom, sulfonic acid group, nitro group, cyano group, fluoroalkyl group, and carboxyl group.

[0012] Based on the fact that R1 and R3 are each independently composed of at least one of sulfonic acid group, fluorocarbon group, nitro group, and cyano group, and that R2 and R4 are each independently composed of hydrogen atoms, the steric hindrance of the binder can be reduced.

[0013] R2 and R4 are each an electron-withdrawing group, which can increase the binding sites with the negative electrode active material particles and improve the adhesion performance.

[0014] In some implementations, R5 to R8 are all hydrogen atoms.

[0015] Therefore, based on the fact that R1 and R3 are each independently composed of at least one of sulfonic acid groups, fluorocarbon groups, nitro groups, and cyano groups, and that R5 to R8 are all hydrogen atoms, the binder can have less steric hindrance. This allows the molecular chains to more flexibly contact and bind to the active sites on the surface of the negative electrode active material particles, forming tighter physical adsorption and chemical bonding, thus improving the bonding effect. Simultaneously, it can reduce the ion transport resistance at the interface between the binder and the negative electrode active material particles, improving charge-discharge performance.

[0016] In some embodiments, the negative electrode sheet includes a negative electrode active material, which includes one or more of silicon-carbon composite materials, silicon oxides, silicon-nitrogen composite materials, elemental silicon, and silicon alloys; the mass percentage of silicon in the negative electrode active material is 40% to 50%.

[0017] In some embodiments, the thickness of the negative electrode active material layer is 20 μm to 80 μm.

[0018] In some embodiments, the bonding strength of the negative electrode sheet is 100 N / m to 500 N / m.

[0019] Therefore, the negative electrode active material layer including the binder of the present disclosure embodiment has good adhesion.

[0020] In some embodiments, the compaction density of the negative electrode active material layer is 0.8 g / cm³. 3 ~1.1g / cm 3 .

[0021] Therefore, by keeping the compaction density of the negative electrode active material layer within the above range, a high-energy-density battery cell can be obtained.

[0022] Secondly, embodiments of this disclosure provide a battery device comprising a plurality of battery cells according to any embodiment of the first aspect of this disclosure.

[0023] Thirdly, embodiments of this disclosure provide an electrical device comprising a plurality of battery cells according to any embodiment of the first aspect of this disclosure or a battery device according to any embodiment of the second aspect of this disclosure.

[0024] Fourthly, embodiments of this disclosure also disclose a method for preparing a battery cell according to any embodiment of the first aspect of this disclosure, comprising:

[0025] Preparation of negative electrode sheet: Provide a binder precursor as shown in formula (II) below, mix the above binder precursor with a conductive agent and a negative electrode active material in a solution to prepare a negative electrode slurry, coat the negative electrode slurry on the surface of at least one side of the current collector, and dry it to obtain a negative electrode sheet.

[0026] The electrode assembly, including the negative electrode plate, is assembled into a single battery cell;

[0027]

[0028] R1 ’ Up to R8 ’ Each independent representation includes at least one of the following: hydrogen atom, sulfonic acid group, nitro group, cyano group, fluoroalkyl group, carboxyl group, acyl group, formyl group, ester group, and amide group; R1 ’ Up to R8 ’ At least one of the following groups is included: sulfonic acid group, nitro group, cyano group, fluoroalkyl group, carboxyl group, acyl group, formyl group, ester group, and amide group.

[0029] Therefore, the present invention introduces the above-mentioned electron-withdrawing groups into the aromatic ring side chain of the polyamic acid compound in the binder precursor. The electron-withdrawing groups are directly connected to the aromatic ring, which can reduce the electron cloud density on the benzene ring, reduce the activation energy of CN bond formation, promote the imidization reaction, and enable the polyamic acid to cyclize at a lower temperature, thereby reducing the crosslinking and curing temperature. For example, after the slurry is coated on the current collector, crosslinking and curing can be completed during the drying process (120°C), reducing equipment investment costs and energy consumption.

[0030] Furthermore, the resulting negative electrode sheet exhibits good adhesion properties, thereby improving the cycle performance of the battery cell.

[0031] In some implementations, R1 ’ Up to R8 ’ At least one of the following groups is selected from sulfonic acid group, nitro group, cyano group, fluoroalkyl group, carboxyl group, acyl group, formyl group, ester group, and amide group.

[0032] In some embodiments, the drying temperature during the preparation of the negative electrode sheet is 100°C to 140°C.

[0033] In some embodiments, the weight-average molecular weight of the binder precursor is 50 kDa to 300 kDa.

[0034] Therefore, the weight-average molecular weight of the binder precursor is within the above range, which has stronger adhesion and mechanical strength, improves the stability of the negative electrode active material particles on the negative electrode sheet, reduces pulverization and detachment, and improves the integrity of the negative electrode sheet.

[0035] In some embodiments, the viscosity of the aqueous solution of the binder precursor with a solid content of 20% is 1500 cP to 3000 cP at 25°C.

[0036] In some embodiments, the adhesive precursor is formed into a 0.5 mm thick film with a tensile strength of 50 MPa to 150 MPa.

[0037] In some embodiments, the adhesive precursor is formed into an adhesive film with a thickness of 0.5 mm and an elongation at break of 10% to 30%.

[0038] Therefore, the binder precursor has high mechanical strength, such as tensile strength and elongation at break, making it suitable for silicon anode materials with large volume expansion. It can alleviate the mechanical stress generated in the silicon anode during cycling and maintain the stability of the ion transport channel.

[0039] In some embodiments, the adhesive precursor is made into a 0.5 mm thick film and immersed in a solvent of ethylene carbonate, diester, and methyl ethyl carbonate in a mass ratio of 1:1:1 for 24 hours at 60°C, and the swelling degree is 10% to 30%.

[0040] Therefore, the binder precursor has good stability in the electrolyte, which can reduce side reactions with the electrolyte, maintain good bonding performance during charge-discharge cycles, reduce the pulverization and shedding of negative electrode active material particles, improve the stability of the negative electrode sheet, and thus improve cycle performance.

[0041] In some embodiments, the mass fraction of the binder precursor is 1% to 10%, based on a total mass fraction of 100% for the binder precursor, conductive agent, and negative electrode active material.

[0042] Therefore, using binder precursors within the aforementioned mass fraction range can give the negative electrode sheet good adhesion and cohesion, slow down the volume expansion of the negative electrode active material particles, suppress structural collapse such as that of silicon negative electrodes during lithiation / delithiation, and improve cycle life. Simultaneously, while using a lower amount of binder precursor to meet the adhesion performance requirements of the negative electrode sheet, it is possible to accommodate negative electrode active material particles with a higher mass fraction, thereby increasing the energy density of the battery cell.

[0043] In some embodiments, the binder precursor comprises at least one of the compounds with structures shown in formulas (II-1) to (II-4):

[0044]

[0045] In some implementations, the electrode assembly includes a negative electrode, a positive electrode, and a separator.

[0046] In some embodiments, the electrode assembly is placed in a housing, an electrolyte is injected, and the assembly is encapsulated and formed to obtain a battery cell. Attached Figure Description

[0047] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings used in the embodiments of this disclosure will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this disclosure. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0048] Figure 1 This is a schematic diagram of a secondary battery cell according to one embodiment of the present disclosure;

[0049] Figure 2 This is a schematic diagram of the structure of a battery device according to one embodiment of the present disclosure;

[0050] Figure 3 yes Figure 2 An exploded view of a battery device according to an embodiment of the present disclosure is shown.

[0051] Figure 4 This is a schematic diagram of an electrical device that uses a secondary battery as a power source according to one embodiment of the present disclosure;

[0052] Figure 5 This is the nuclear magnetic resonance spectrum of the binder precursor of Embodiment 1 of this disclosure;

[0053] Figure 6 This is the EDS diagram of the negative electrode sheet of Embodiment 1 of this disclosure.

[0054] The annotations in the attached figures are explained as follows:

[0055] 1. Battery assembly; 2. Upper housing; 3. Lower housing; 4. Battery module; 5. Secondary battery;

[0056] The accompanying drawings are not necessarily drawn to scale. Detailed Implementation

[0057] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the conductive paste, current collector, secondary battery, battery module, battery device, and power supply device of this disclosure. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this disclosure and are not intended to limit the subject matter of the claims.

[0058] The "range" disclosed in this disclosure is defined by a lower limit and an upper limit, whereby a given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also expected. Furthermore, if minimum range values ​​1 and 2 are listed, and if maximum range values ​​3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this disclosure, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0059] Unless otherwise specified, all embodiments and optional embodiments of this disclosure can be combined to form new technical solutions.

[0060] Unless otherwise specified, all technical features and optional technical features of this disclosure can be combined to form new technical solutions.

[0061] Unless otherwise specified, all steps of this disclosure may be performed sequentially or randomly, preferably sequentially. For example, if a method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if it is mentioned that the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0062] Unless otherwise specified, the terms "comprising" and "including" as used in this disclosure can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0063] Unless otherwise specified, the term "or" is inclusive in this disclosure. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0064] Unless otherwise specified, in this disclosure, the terms "first," "second," etc., are used to distinguish different objects, rather than to describe a specific order or primary / secondary relationship.

[0065] In this disclosure, the terms "multiple" or "a variety" refer to two or more kinds.

[0066] In the description of the embodiments of this disclosure, unless otherwise specified, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0067] Unless otherwise stated, the test temperature for all parameters mentioned in this disclosure is 25°C.

[0068] The secondary battery cell mentioned in the embodiments of this disclosure can independently perform charge and discharge functions. After discharge, it can be reactivated by charging to allow for continued use. The secondary battery cell can be cylindrical, cuboid, or other shapes, and the embodiments of this disclosure are not limited in this regard. Figure 1 This is a cuboid-shaped secondary battery cell used as an example.

[0069] The secondary battery cells provided in the embodiments of this disclosure may include, but are not limited to, lithium battery cells and sodium battery cells, such as lithium-ion battery cells, sodium-ion battery cells, lithium metal battery cells, sodium metal battery cells, etc. The secondary battery cells provided in the embodiments of this disclosure include electrode assemblies.

[0070] The electrode assembly can be a wound structure or a stacked structure, and this disclosure does not limit this. The secondary battery cell also includes an outer packaging, which can be used to encapsulate the electrode assembly. The outer packaging can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging can also be a flexible package, such as a pouch. The material of the flexible package can be plastic, such as one or more of aluminum-plastic film, polypropylene, polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0071] The battery apparatus mentioned in the embodiments of this disclosure may include one or more battery cell assemblies for providing voltage and capacity. A battery cell assembly may include multiple secondary battery cells connected in series, parallel, or mixed connections via a busbar. In some embodiments, the battery cell assembly is typically formed by arranging multiple secondary battery cells.

[0072] As an example, a battery cell assembly can be a battery module, which is formed by arranging and fixing multiple secondary battery cells together to form an independent module. As another example, a battery module can be formed by bundling multiple secondary battery cells together with cable ties.

[0073] The large volume expansion of silicon anodes leads to poor battery cycle performance. Common binders such as carboxymethyl cellulose (CMC) and styrene-butadiene latex (SBR) are used on pure silicon high-silicon anodes, but the battery cycle performance remains poor. While increasing the amount of conductive carbon black and SBR can suppress the expansion and cracking effects of silicon particles during cycling, this reduces the mass fraction of the anode active material in the anode sheet, affecting the energy density of the battery cell.

[0074] In view of the above problems, this disclosure proposes a battery cell. The battery cell includes a negative electrode sheet, the negative electrode sheet includes a current collector and a negative active material layer stacked together, and the negative active material layer includes a binder, the binder including a compound having the structure shown in formula (I).

[0075]

[0076] Each of R1 to R8 independently represents at least one of the following: hydrogen atom, sulfonic acid group, nitro group, cyano group, fluoroalkyl group, carboxyl group, acyl group, formyl group, ester group, and amide group; at least one of R1 to R8 includes one of the following: sulfonic acid group, nitro group, cyano group, fluoroalkyl group, carboxyl group, acyl group, formyl group, ester group, and amide group.

[0077] The benzene ring and imide structure in the binder possesses excellent mechanical and tensile strength. Introducing electron-withdrawing groups, such as those mentioned above, directly into the aromatic ring side chains can enhance the interfacial bonding between the binder and the negative electrode active material, such as silicon-based materials. For example, nitro groups can enhance the adhesion between the binder and the negative electrode, suppressing the volume expansion of silicon during cycling. Cyano-containing polymers have better elasticity, increasing the mechanical flexibility of the electrode and thus adapting to changes in the negative electrode volume. The high polarity and strong hydrogen bonding of sulfonic acid groups can improve the adhesion between the binder and the negative electrode active material, effectively suppressing volume expansion during charge and discharge, reducing crack formation, and extending cycle life. Carboxyl groups are coordinated with the surface of the negative electrode active material, exhibiting good adaptability to volume changes. Acyl groups can form a cross-linked network through condensation reactions, enhancing the mechanical strength of the binder and suppressing the volume expansion of the negative electrode active material. Therefore, the structural stability of the negative electrode active material layer is strengthened, improving the battery's cycle performance.

[0078] The technical solutions of the embodiments disclosed herein will be described in detail below.

[0079] [Negative electrode plate]

[0080] In some embodiments, the battery cell includes a negative electrode sheet, which includes a current collector and a negative active material layer stacked together, and the negative active material layer includes a binder, which includes a compound having the structure shown in formula (I) above.

[0081] In some embodiments, R1 and R3 each independently include at least one of sulfonic acid group, fluoroalkyl group, nitro group, and cyano group.

[0082] In some embodiments, R1 and R3 are each independently selected from at least one of sulfonic acid group, fluoroalkyl group, nitro group, and cyano group.

[0083] R1 and R3, each consisting of groups directly linked to a benzene ring and concentrated on one side, enable the binder to form a more directional and selective interaction with the silicon material surface. This facilitates a more ordered arrangement of the binder molecular chains on the silicon surface, resulting in a denser and more regular adhesive layer, further enhancing the bonding effect and strengthening the stability of the electrode structure. On the other hand, sulfonic acid groups, in addition to being electron-withdrawing groups that can dissociate protons, can also promote lithium-ion conduction, improving the conductivity of the binder and thus enhancing the kinetic performance of the electrode.

[0084] In some embodiments, R2 and R4 each independently include at least one of hydrogen atom, sulfonic acid group, nitro group, cyano group, fluoroalkyl group, and carboxyl group.

[0085] Based on the fact that R1 and R3 are each independently composed of at least one of sulfonic acid group, fluorocarbon group, nitro group, and cyano group, and that R2 and R4 are each independently composed of hydrogen atoms, the steric hindrance of the binder can be reduced.

[0086] R2 and R4 are each an electron-withdrawing group, which can increase the binding sites with the negative electrode active material particles and improve the adhesion performance.

[0087] In some implementations, R5 to R8 are all hydrogen atoms.

[0088] Based on the fact that R1 and R3 are each independently composed of at least one of sulfonic acid groups, fluorocarbon groups, nitro groups, and cyano groups, and that R5 to R8 are all hydrogen atoms, the binder can have less steric hindrance. This allows the molecular chains to more flexibly contact and bind to the active sites on the surface of the negative electrode active material particles, forming tighter physical adsorption and chemical bonds, thus improving the bonding effect. Simultaneously, it can reduce the ion transport resistance at the interface between the binder and the negative electrode active material particles, improving charge-discharge performance.

[0089] In some embodiments, the negative electrode sheet includes a negative electrode active material, which includes one or more of silicon-carbon composite materials, silicon oxides, silicon-nitrogen composite materials, elemental silicon, and silicon alloys; the mass fraction of silicon in the negative electrode active material is 40%-50%. By using a relatively small amount of binder, the mass fraction of silicon-based material in the negative electrode sheet is increased, thereby improving the energy density of the battery cell.

[0090] For example, the mass fraction of silicon in the negative electrode active material can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, or any range of two of the above values.

[0091] In some embodiments, the thickness of the negative electrode active material layer is 20 μm to 80 μm.

[0092] For example, the thickness of the negative electrode active material layer can be 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm or any range of two of the above values.

[0093] In some embodiments, the adhesion strength of the negative electrode sheet is 100 N / m to 500 N / m. The negative electrode active material layer including the binder of the embodiments of this disclosure has good adhesion strength.

[0094] For example, the adhesion strength of the negative electrode active material layer can be 100 N / m, 150 N / m, 200 N / m, 250 N / m, 300 N / m, 350 N / m, 400 N / m, 450 N / m, 500 N / m or any range of two of the above values.

[0095] In some embodiments, the compaction density of the negative electrode active material layer is 0.8 g / cm³. 3 ~1.1g / cm 3 When the compaction density of the negative electrode active material layer is within the above range, high-energy-density battery cells can be obtained.

[0096] For example, the compaction density of the negative electrode active material layer can be 0.8 g / cm³. 3 0.82g / cm 3 0.84 g / cm 3 0.86 g / cm 3 0.88g / cm 3 0.9g / cm 3 0.92g / cm 3 0.94g / cm 3 0.96g / cm 3 0.98g / cm 3 1.0g / cm 3 1.02g / cm 3 1.04 g / cm 3 1.06 g / cm 3 1.08g / cm 3 1.1g / cm 3 Or a range consisting of any two of the above values.

[0097] In some embodiments, the negative electrode active material layer further includes one or more of polyacrylic acid (PAA), sodium alginate (Alg), cyclodextrin, styrene-butadiene rubber (SBR), carboxymethyl chitosan (CMCS), and polyvinylidene fluoride (PVDF).

[0098] In some implementations, the current collector of the negative electrode can be a metal foil, a three-dimensional porous current collector, or a composite current collector.

[0099] Examples of metal foils include copper foil, copper alloy foil, nickel foil, nickel alloy foil, aluminum foil, and aluminum alloy foil. Examples of three-dimensional porous current collectors include copper mesh, nickel mesh, aluminum mesh, copper foam, nickel foam, and aluminum foam. Composite current collectors may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As examples, the metal material may include, but is not limited to, one or more of copper, copper alloys, aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As examples, the polymer material base layer may include, but is not limited to, one or more of polypropylene, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene, and polyethylene.

[0100] In some embodiments, the negative electrode conductive agent may be one or more of the following, including but not limited to conductive graphite (such as KS-6, SFG-6), superconducting carbon, acetylene black, carbon black (such as SP), Ketjen black (such as ECP), carbon dots, carbon nanotubes, graphene, carbon nanofibers, and vapor-grown carbon fibers (VGCF).

[0101] Polyamic acid polymers possess good thermal and chemical stability, high mechanical strength, and are well-suited for silicon anode materials with large volume expansion. However, their imidization temperature is high, and to function as a binder and suppress silicon particle expansion in the electrode, a further high-temperature curing reaction is required to generate polyimide. This step typically requires high-temperature conditions (around 300°C) and an inert atmosphere (vacuum or nitrogen) to complete the reaction, resulting in high production costs.

[0102] This disclosure also discloses a method for preparing a single battery cell, comprising:

[0103] Preparation of negative electrode sheet: Provide a binder precursor as shown in formula (II) below, mix the above binder precursor with a conductive agent and a negative electrode active material in a solution to prepare a negative electrode slurry, coat the negative electrode slurry on the surface of at least one side of the current collector, and dry it to obtain a negative electrode sheet.

[0104] The electrode assembly, including the negative electrode plate, is assembled into a single battery cell;

[0105]

[0106] R1 ’ Up to R8 ’ Each independent representation includes at least one of the following: hydrogen atom, sulfonic acid group, nitro group, cyano group, fluoroalkyl group, carboxyl group, acyl group, formyl group, ester group, and amide group; R1 ’ Up to R8 ’At least one of the following groups is included: sulfonic acid group, nitro group, cyano group, fluoroalkyl group, carboxyl group, acyl group, formyl group, ester group, and amide group.

[0107] The present invention discloses an adhesive precursor by introducing the aforementioned electron-withdrawing groups into the aromatic ring side chain of a polyamic acid compound. These electron-withdrawing groups are directly connected to the aromatic ring, which can reduce the electron cloud density on the benzene ring, lower the activation energy of CN bond formation, promote the imidization reaction, and enable the polyamic acid to cyclize at a lower temperature, thereby reducing the crosslinking and curing temperature. For example, after the slurry is coated on the current collector, crosslinking and curing can be completed during the tunnel oven drying process (120°C), reducing equipment investment costs and energy consumption.

[0108] Furthermore, the resulting negative electrode sheet exhibits good adhesion properties, thereby improving the cycle performance of the battery cell.

[0109] In some implementations, R1 ’ Up to R8 ’ At least one of the following groups is selected from sulfonic acid group, nitro group, cyano group, fluoroalkyl group, carboxyl group, acyl group, formyl group, ester group, and amide group.

[0110] In some embodiments, the drying temperature during the preparation of the negative electrode sheet is 100°C to 140°C.

[0111] In some embodiments, the degree of polymerization of the binder precursor is 100 to 600, optionally 200 to 500.

[0112] When the degree of polymerization of the binder precursor is within the above range, there are more cross-linking points, which can form a stable and compact cross-linking network, resulting in stronger adhesion, better suppression of the volume expansion of the negative electrode active material particles, and improved cycle performance.

[0113] For example, the degree of polymerization of the adhesive precursor can be 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600 or any range of two of the above values.

[0114] In some embodiments, the weight-average molecular weight of the binder precursor is 50 kDa to 300 kDa, and optionally 100 kDa to 250 kDa.

[0115] The weight-average molecular weight of the binder precursor is within the above range, which has stronger adhesion and mechanical strength, improves the stability of the negative electrode active material particles on the negative electrode sheet, reduces pulverization and detachment, and improves the integrity of the negative electrode sheet.

[0116] For example, the weight-average molecular weight of the binder precursor can be 50 kDa, 75 kDa, 100 kDa, 125 kDa, 150 kDa, 175 kDa, 200 kDa, 225 kDa, 250 kDa, 275 kDa, 300 kDa, or any range of two of the above values.

[0117] In some embodiments, the aqueous solution of the binder precursor with a solid content of 20% has a viscosity of 1500 cP to 3000 cP at 25°C.

[0118] For example, the viscosity of an aqueous solution of a binder precursor with a solid content of 20% at 25°C can be 1500 cP, 1600 cP, 1700 cP, 1800 cP, 1900 cP, 2000 cP, 2100 cP, 2200 cP, 2300 cP, 2400 cP, 2500 cP, 2600 cP, 2700 cP, 2800 cP, 2900 cP, 3000 cP, or any range of two of the above values.

[0119] In some embodiments, the adhesive precursor is formed into a 0.5 mm thick film with a tensile strength of 50 MPa to 150 MPa.

[0120] For example, the tensile strength of the adhesive precursor formed into a 0.5 mm thick film can be 50 MPa, 60 MPa, 70 MPa, 80 MPa, 90 MPa, 100 MPa, 110 MPa, 120 MPa, 130 MPa, 140 MPa, 150 MPa or any combination of two of the above values.

[0121] In some embodiments, the adhesive precursor is formed into an adhesive film with a thickness of 0.5 mm and an elongation at break of 10% to 30%.

[0122] The binder precursor has high mechanical strength, such as tensile strength and elongation at break, making it suitable for silicon anode materials with large volume expansion. It can alleviate the mechanical stress generated in the silicon anode during cycling and maintain the stability of the ion transport channel.

[0123] For example, the elongation at break of the adhesive precursor to form a 0.5 mm thick film can be 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, or any combination of two of the above values.

[0124] In some embodiments, the adhesive precursor is made into a 0.5 mm thick film and immersed in a solvent of ethylene carbonate, diester, and methyl ethyl carbonate in a mass ratio of 1:1:1 at 60°C for 24 hours, and the swelling degree is 10% to 30%, optionally 15% to 20%.

[0125] The binder precursor has good stability in the electrolyte, which can reduce side reactions with the electrolyte, maintain good bonding performance during charge-discharge cycles, reduce the pulverization and shedding of negative electrode active material particles, improve the stability of the negative electrode sheet, and thus improve cycle performance.

[0126] For example, the degree of swelling can be 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, or a range of any two of the above values.

[0127] In some embodiments, the mass fraction of the binder precursor is 1% to 10%, based on a total mass fraction of 100% for the binder precursor, conductive agent, and negative electrode active material.

[0128] For example, the mass fraction of the adhesive precursor can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any combination of two of the above values.

[0129] Using binder precursors within the aforementioned mass fraction range can give the negative electrode sheet good adhesion and cohesion, slow down the volume expansion of the negative electrode active material particles, suppress structural collapse such as that of silicon negative electrodes during lithiation / delithiation, and improve cycle life. Simultaneously, while using a lower amount of binder to meet the adhesion performance of the negative electrode sheet, it is possible to accommodate negative electrode active material particles with a higher mass fraction, thereby increasing the energy density of the battery cell.

[0130] In some embodiments, the binder precursor has at least one of the compounds with structures shown in formulas (II-1) to (II-4):

[0131]

[0132] In some implementations, the electrode assembly includes a negative electrode, a positive electrode, and a separator.

[0133] In some embodiments, the electrode assembly is placed in a housing, an electrolyte is injected, and the assembly is encapsulated and formed to obtain a battery cell.

[0134] In some implementations, the electrode assembly includes a negative electrode, a positive electrode, and a separator.

[0135] In some embodiments, the electrode assembly is placed in a housing, an electrolyte is injected, and the assembly is encapsulated and formed to obtain a battery cell.

[0136] [Electrolytes]

[0137] In some implementations, the battery cell also includes an electrolyte.

[0138] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and an organic solvent.

[0139] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0140] In some embodiments, the organic solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone. The solvent may also be an ether solvent. Ether solvents may include one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, methyl tetrahydrofuran, diphenyl ether, and crown ethers.

[0141] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain properties of the battery cell, such as additives that improve the overcharge / fast charge performance of the battery cell, additives that improve the high-temperature performance of the battery cell, and additives that improve the low-temperature performance of the battery cell.

[0142] [Positive electrode plate]

[0143] In some embodiments, the battery cell further includes a positive electrode sheet, which includes a positive current collector and a positive active material layer stacked together, the positive active material layer including a positive active material.

[0144] In some embodiments, the positive electrode active material may include, but is not limited to, one or more of lithium transition metal oxides, metal chalcogenides, lithium-containing phosphates, and their respective modified compounds.

[0145] Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides, lithium nickel oxides, lithium manganese oxides, lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, lithium nickel cobalt manganese oxides, lithium nickel cobalt aluminum oxides, lithium titanium oxides, and one or more of their respective modified compounds.

[0146] Lithium transition metal oxides can include, but are not limited to, layered structures and spinel structures.

[0147] Examples of lithium phosphates may include, but are not limited to, lithium iron phosphate, lithium iron phosphate and carbon composites, lithium manganese phosphate, lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, lithium manganese iron phosphate and carbon composites, and one or more of their respective modified compounds.

[0148] In some embodiments, to further improve the energy density of a single battery cell, the positive electrode active material may include materials with the general formula Li. a Ni b Co c M d O e D f One or more of lithium transition metal oxides and their modified compounds. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M may include, but is not limited to, one or more of Ge, Mo, Sn, Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and D may include, but is not limited to, one or more of N, F, S and Cl.

[0149] In some embodiments, the positive electrode active material may simultaneously comprise lithium transition metal oxide and lithium phosphate. This is advantageous for obtaining battery cells that balance high capacity and high reliability.

[0150] As an example, the positive electrode active material may include, but is not limited to, LiCoO2, LiNiO2, LiMnO2, and LiNi 1 / 2 Mn 1 / 2O2, LiMn2O4, Li 4 / 3 Ti 5 / 3 O4, LiNi 1 / 2 Mn 1 / 2 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.92 Co 0.05 Mn 0.03 O2(Ni92), LiNi 0.96 Co 0.03 Mn 0.01 O2(Ni96), LiNi0.80 Co 0.15 Al 0.05 O2(NCA), LiFePO4, LiMnPO4, Li 1.13 Ti 0.57 Fe 0.3 One or more of S2.

[0151] In some embodiments, the positive electrode active material layer further includes a conductive agent. The conductive agent may be one or more of the following: conductive graphite (such as KS-6, SFG-6), superconducting carbon, acetylene black, carbon black (such as SP), Ketjen black (such as ECP), carbon dots, carbon nanotubes, graphene, carbon nanofibers, and vapor-grown carbon fibers (VGCF).

[0152] In some embodiments, the positive electrode active material layer further includes a binder. The positive electrode binder may include, but is not limited to, one or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylate resin, water-soluble unsaturated resin SR-1B, methyl vinyl silicone rubber, nitrile butadiene rubber (NBR), hydrogenated nitrile butadiene rubber (HNBR), styrene-butadiene rubber (SBR), thermoplastic styrene-butadiene rubber (SBS), isoprene rubber, cis-butadiene rubber (BR), ethyl cellulose, polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), carboxymethyl chitosan (CMCS), fluororubber, and acrylate rubber.

[0153] In some embodiments, the positive current collector can be a metal foil or a composite current collector. Examples of metal foils include stainless steel foil, carbon-coated aluminum foil, aluminum foil, nickel foil, and titanium foil. The composite current collector can include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. Examples of metal materials include, but are not limited to, one or more of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. Examples of polymer substrates include, but are not limited to, one or more of polypropylene, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene.

[0154] [Isolation Component]

[0155] In some implementations, the battery cell also includes a separator disposed between the positive and negative electrodes.

[0156] In some embodiments, the separator is a separator membrane. This disclosure does not impose any particular limitation on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected.

[0157] As an example, the main material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride, and ceramic. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation. The separator can be a single component located between the positive and negative electrodes, or it can be attached to the surfaces of the positive and negative electrodes. An inorganic particle coating, an organic particle coating, or an organic / inorganic composite coating can also be applied to the surface of the separator.

[0158] In some embodiments, the separator is a solid electrolyte. The solid electrolyte is disposed between the positive and negative electrodes, serving both to transport ions and to isolate the positive and negative electrodes.

[0159] Battery device

[0160] Secondly, embodiments of this disclosure provide a battery device comprising a plurality of battery cells according to any embodiment of the first aspect of this disclosure.

[0161] Figure 2 This is a schematic diagram of a battery device as an example. Figure 3 yes Figure 2 The diagram shown is an exploded view of a battery device as an example. The battery device may include a battery housing and multiple battery modules disposed within the battery housing. The battery housing includes an upper housing and a lower housing, the upper housing covering the lower housing and forming a closed space for accommodating the battery modules. The multiple battery modules can be arranged in any manner within the battery housing.

[0162] Electrical appliances

[0163] A third aspect of this disclosure provides an electrical device, which includes at least one of a battery cell, a battery module, or a battery device according to this disclosure. The battery cell, battery module, or battery device can be used as a power source for the electrical device or as an energy storage unit of the electrical device. The electrical device can be, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0164] Electrical devices can be equipped with individual battery cells, battery modules, or battery packs depending on their usage requirements.

[0165] Figure 4 This is a schematic diagram illustrating an example of an electrical device. This device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the device's requirements for high power and high energy density, a battery device or battery module can be used.

[0166] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.

[0167] Example

[0168] The following embodiments describe the contents disclosed in this disclosure in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0169] Example 1

[0170] 1. Preparation of positive electrode sheet

[0171] The positive electrode sheet includes a positive current collector and a positive active material layer. The positive current collector is aluminum foil, and the positive active material LiNi is added according to a certain mass ratio. 0.92 Co 0.05 Mn 0.03 A positive electrode slurry was prepared by dissolving O2, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride (PVDF) binder in a ratio of 98:0.8:0.2:1 in N-methylpyrrolidone. The slurry had a solid content of 75% and a viscosity of 5000 cP. This positive electrode slurry was then uniformly coated onto the surface of an aluminum foil current collector, and after drying and cold pressing, a positive electrode sheet was obtained.

[0172] 2. Preparation of negative electrode sheet

[0173] 2.1 Preparation of binder precursors

[0174] 3,5-Disulfonic-4,4'-diaminodiphenyl ether was dissolved in dimethylformamide and stirred in an ice-water bath under a nitrogen atmosphere until completely dissolved. After the solution became homogeneous and transparent, pyromellitic dianhydride was added in three batches at a molar ratio of 1:1 to pyromellitic dianhydride. Stirring continued in the ice-water bath to avoid vigorous exothermic reactions. The temperature was slowly increased to 25°C to accelerate the polycondensation reaction. Viscosity samples were taken periodically and tested. The reaction was stopped when the viscosity reached 5000 cp. Impurities were removed by filtration through a 0.45 μm filter membrane. Twice the volume of ethyl acetate was added to precipitate polyamic acid. The precipitate was obtained by suction filtration and washed three times with ethyl acetate to obtain the binder precursor.

[0175] 2.2 Preparation of negative electrode sheet

[0176] A negative electrode slurry was prepared using the aforementioned binder precursor. The negative electrode active material (including a silicon-carbon composite material (a porous carbon-deposited nano-silicon coated with amorphous carbon) and graphite in a mass ratio of 9:1, with silicon comprising 45% by mass) was mixed with conductive carbon black, carbon nanotubes, and binder precursor in a ratio of 95:1.5:0.5:3. Deionized water was then added, and the mixture was stirred to obtain the negative electrode slurry. The solid content of the negative electrode slurry was 45%, and the viscosity was 5000 cP. The negative electrode slurry was uniformly coated onto the surface of a current collector copper foil, dried at 120°C for 30 minutes, and cold-pressed to obtain a negative electrode sheet. During the drying process, the binder precursor underwent an imidization reaction and cross-linking curing, resulting in a binder with the structure shown in Example 1 of Table 1 within the negative electrode sheet.

[0177] 3. Separating membrane

[0178] 7μm uncoated polyethylene (PE) film.

[0179] 4. Preparation of electrolyte

[0180] The electrolyte consists of an organic solvent and a lithium salt. The electrolyte is a solution of ethylene carbonate / ethyl methyl carbonate (EC / EMC, mass ratio 3:7) containing 1 mol / L LiPF6.

[0181] 5. Preparation of battery cells

[0182] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator acting as a separator between the positive and negative electrodes. The electrode assembly is then wound up to obtain an electrode assembly. The electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping, a lithium-ion battery cell is obtained.

[0183] Examples 2-9

[0184] The difference between Examples 2-9 and Example 1 lies in the preparation method of the binder precursor, as detailed below.

[0185] Example 2

[0186] 3,5-Disulfonic-4,4'-diaminodiphenyl ether was dissolved in dimethylformamide and stirred in an ice-water bath under a nitrogen atmosphere until completely dissolved. After the solution became homogeneous and transparent, pyromellitic dianhydride was added in three batches, with a molar ratio of 5-disulfonic-4,4'-diaminodiphenyl ether to pyromellitic dianhydride of 1:1. Stirring continued in the ice-water bath to avoid vigorous exothermic reactions. The temperature was slowly increased to 25°C to accelerate the polycondensation reaction. The viscosity was measured at regular intervals, and the reaction was stopped when the viscosity of the reaction system reached 3500 cp. Impurities were removed by filtration through a 0.45 μm filter membrane. Twice the volume of ethyl acetate was added to precipitate polyamic acid. The precipitate was obtained by suction filtration and washed three times with ethyl acetate to obtain the binder precursor.

[0187] Example 3

[0188] 3,5-Disulfonic-4,4'-diaminodiphenyl ether was dissolved in dimethylformamide and stirred in an ice-water bath under a nitrogen atmosphere until completely dissolved. After the solution became homogeneous and transparent, pyromellitic dianhydride was added in three batches, with a molar ratio of 5-disulfonic-4,4'-diaminodiphenyl ether to pyromellitic dianhydride of 1:1. Stirring continued in the ice-water bath to avoid violent exothermic reactions. The temperature was slowly increased to 25°C to accelerate the polycondensation reaction. The viscosity was measured at regular intervals, and the reaction was stopped when the viscosity of the reaction system reached 6000 cp. Impurities were removed by filtration through a 0.45 μm filter membrane. Twice the volume of ethyl acetate was added to precipitate polyamic acid. The precipitate was obtained by suction filtration and washed three times with ethyl acetate to obtain the binder precursor.

[0189] Example 4

[0190] 3,5-Disulfonic-4,4'-diaminodiphenyl ether was dissolved in dimethylformamide and stirred in an ice-water bath under a nitrogen atmosphere until completely dissolved. After the solution became homogeneous and transparent, pyromellitic dianhydride was added in three batches, with a molar ratio of 5-disulfonic-4,4'-diaminodiphenyl ether to pyromellitic dianhydride of 1:1. Stirring continued in the ice-water bath to avoid violent exothermic reactions. The temperature was slowly increased to 25°C to accelerate the polycondensation reaction. The viscosity was measured at regular intervals, and the reaction was stopped when the viscosity of the reaction system reached 8000 cp. Impurities were removed by filtration through a 0.45 μm filter membrane. Twice the volume of ethyl acetate was added to precipitate polyamic acid. The precipitate was obtained by suction filtration and washed three times with ethyl acetate to obtain the binder precursor.

[0191] Example 5

[0192] 2,3,5,6-2',3'5',6'-octanitro-4,4'-diaminodiphenyl ether was dissolved in dimethylformamide and stirred in an ice-water bath under a nitrogen atmosphere until completely dissolved. After the solution became homogeneous and transparent, pyromellitic dianhydride was added in three batches, with a molar ratio of 2,3,5,6-2',3'5',6'-octanitro-4,4'-diaminodiphenyl ether to pyromellitic dianhydride of 1:1. Stirring continued in an ice-water bath to avoid violent exothermic reactions. The temperature was slowly increased to 15°C to accelerate the polycondensation reaction. The viscosity was measured periodically, and the reaction was stopped when the viscosity of the reaction system reached approximately 4000 cp. Impurities were removed by filtration through a 0.45 μm filter membrane. Twice the volume of ethyl acetate was added to precipitate polyamic acid. The precipitate was obtained by suction filtration and washed three times with ethyl acetate to obtain the binder precursor.

[0193] Example 6

[0194] 2,3,5,6-2',3'5',6'-octanitro-4,4'-diaminodiphenyl ether was dissolved in dimethylformamide and stirred in an ice-water bath under a nitrogen atmosphere until completely dissolved. After the solution became homogeneous and transparent, pyromellitic dianhydride was added in three batches, with a molar ratio of 2,3,5,6-2',3'5',6'-octanitro-4,4'-diaminodiphenyl ether to pyromellitic dianhydride of 1:1. Stirring continued in an ice-water bath to avoid violent exothermic reactions. The temperature was slowly increased to 15°C to accelerate the polycondensation reaction. The viscosity was measured periodically, and the reaction was stopped when the viscosity of the reaction system reached 3000 cp. Impurities were removed by filtration through a 0.45 μm filter membrane. Twice the volume of ethyl acetate was added to precipitate polyamic acid. The precipitate was obtained by suction filtration and washed three times with ethyl acetate to obtain the binder precursor.

[0195] Example 7

[0196] 2,6-Diacrylonitrile-4,4'-diaminodiphenyl ether was dissolved in dimethylformamide and stirred in an ice-water bath under a nitrogen atmosphere until completely dissolved. After the solution became homogeneous and transparent, pyromellitic dianhydride was added in three batches at a molar ratio of 1:1 to pyromellitic dianhydride. Stirring continued in the ice-water bath to avoid vigorous exothermic reactions. The temperature was slowly increased to 30°C to accelerate the polycondensation reaction. Viscosity samples were taken periodically to test the viscosity. The reaction was stopped when the viscosity reached 5000 cp. Impurities were removed by filtration through a 0.45 μm filter membrane. Twice the volume of ethyl acetate was added to precipitate polyamic acid. The precipitate was obtained by suction filtration and washed three times with ethyl acetate to obtain the binder precursor.

[0197] Example 8

[0198] 2,6-Diacryl-4,4'-diaminodiphenyl ether was dissolved in dimethylformamide and stirred in an ice-water bath under a nitrogen atmosphere until completely dissolved. After the solution became homogeneous and transparent, pyromellitic dianhydride was added in three batches at a molar ratio of 1:1 to pyromellitic dianhydride. Stirring continued in the ice-water bath to avoid vigorous exothermic reactions. The temperature was slowly increased to 30°C to accelerate the polycondensation reaction. Viscosity samples were taken periodically to test the viscosity. The reaction was stopped when the viscosity reached 4000 cp. Impurities were removed by filtration through a 0.45 μm filter membrane. Twice the volume of ethyl acetate was added to precipitate polyamic acid. The precipitate was obtained by suction filtration and washed three times with ethyl acetate to obtain the binder precursor.

[0199] Example 9

[0200] 2,3,5,6-Tetra(trifluoromethyl)-4,4'-diaminodiphenyl ether was dissolved in dimethylformamide and stirred in an ice-water bath under a nitrogen atmosphere until completely dissolved. After the solution became homogeneous and transparent, pyromellitic dianhydride was added in three batches, with a molar ratio of 2,3,5,6-tetra(trifluoromethyl)-4,4'-diaminodiphenyl ether to pyromellitic dianhydride of 1:1. Stirring continued in the ice-water bath to avoid violent exothermic reactions. The temperature was slowly increased to 25°C to accelerate the polycondensation reaction. The viscosity was measured periodically, and the reaction was stopped when the viscosity of the reaction system reached 7000 cp. Impurities were removed by filtration through a 0.45 μm filter membrane. Twice the volume of ethyl acetate was added to precipitate polyamic acid. The precipitate was obtained by suction filtration and washed three times with ethyl acetate to obtain the binder precursor.

[0201] Example 10

[0202] 3-Sulfoethyl-4,4'-diaminodiphenyl ether was dissolved in dimethylformamide and stirred in an ice-water bath under a nitrogen atmosphere until completely dissolved. After the solution became homogeneous and transparent, pyromellitic dianhydride was added in three batches at a molar ratio of 1:1 to pyromellitic dianhydride. Stirring continued in the ice-water bath to avoid vigorous exothermic reactions. The temperature was slowly increased to 30°C to accelerate the polycondensation reaction. Viscosity samples were taken periodically to test the viscosity. The reaction was stopped when the viscosity reached 6000 cp. Impurities were removed by filtration through a 0.45 μm filter membrane. Twice the volume of ethyl acetate was added to precipitate polyamic acid. The precipitate was obtained by suction filtration and washed three times with ethyl acetate to obtain the binder precursor.

[0203] Comparative Examples 1-4

[0204] Lithium-ion battery cells were prepared using a method similar to that of Example 1. However, the type of binder was different compared to Example 1, and the technical parameters that changed during the preparation process are shown in Table 1.

[0205] Performance testing

[0206] (1) Weight-average molecular weight test of binder precursor

[0207] The weight-average molecular weight of the binder precursor prepared above was determined by high performance liquid chromatography using a Waters e2695 high performance liquid chromatograph.

[0208] (3) Nuclear magnetic resonance characterization

[0209] Deuterated DMSO was used as a solvent to dissolve the binder precursor, and tetramethylsilane (TMS) was used as an internal standard for NMR analysis. ¹H NMR spectra were collected on a Bruker Avance III 600MHz NMR spectrometer equipped with a 5mm probe. Data acquisition and signal integration were performed using TopSpin software, and further data processing was conducted using MestRe-C software.

[0210] Figure 5 This is the NMR spectrum of the binder precursor in Example 1, from... Figure 5 As can be seen, the peak at chemical shift 12.39 represents the H on the carboxyl group (-COOH), indicating that the binder precursor has not yet been imidized; the peak at chemical shift 10.8 represents the H on the imino group (-NH); the peaks at chemical shifts 6.86-8.45 represent H peaks on the benzene ring, with peaks >8 representing H on the benzene ring of pyromellitic acid, and peaks around 7 representing H on the benzene ring of diphenyl ether; peaks less than 4 represent H peaks on aliphatic hydrocarbons. Under these near-neutral pH NMR detection conditions, the H on the sulfonic acid group has been substituted, but from... Figure 6 It is evident that the negative electrode contains sulfur (S).

[0211] (4) Swelling property test of binder precursor

[0212] An appropriate amount of adhesive precursor was placed in a polytetrafluoroethylene petri dish and baked in a forced-air drying oven at 105°C for 24 hours to obtain a polymer film with a thickness of 0.5 mm.

[0213] The obtained polymer film was immersed in a carbonate solvent at a predetermined temperature for a predetermined time, and then removed. The swelling degree was calculated according to the formula: Swelling degree = (mass after immersion - mass before immersion) / mass before immersion × 100%. The carbonate solvent was prepared as follows: ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate were mixed evenly in a mass ratio of 1:1:1.

[0214] (5) Viscosity test of binder precursor

[0215] At 25℃, the binder precursor was poured into a special sample cup and kept at a constant temperature to be tested. The viscosity of the binder precursor solution was tested using a Bollerfeld (DV-2TLV) viscometer with a solid content of 20%. The corresponding rotor speed was selected according to the sample viscosity range. The Multi Point data acquisition mode was selected, and automatic detection was started. Three measurements were taken and the average value was taken.

[0216] (6) Compaction density test of negative electrode active material layer

[0217] Take a single-sided coated and cold-pressed negative electrode sheet, punch it into a small circular piece with an area of ​​S1, weigh it, and record its weight as M1. Then wipe off the negative electrode active material layer of the weighed negative electrode sheet, weigh the negative electrode current collector, and record it as M0. The areal density of the negative electrode active material layer = (weight of negative electrode sheet M1 - weight of negative electrode current collector M0) / S1, and the compaction density of the negative electrode active material layer = areal density of negative electrode active material layer / thickness of negative electrode active material layer.

[0218] (7) Adhesion test of negative electrode sheet

[0219] Referring to the national standard "Test Method for 180° Peel Strength of Adhesives", the adhesion test process for the negative electrode sheet in this embodiment and comparative example is as follows: A sample with a width of 30mm and a length of 100-160mm is cut with a blade. Special double-sided adhesive tape is applied to a steel plate, with a tape width of 20mm and a length of 90-150mm. The previously cut electrode sheet sample is then placed on the double-sided adhesive tape, test side down, and rolled three times in the same direction using a pressure roller. A paper strip with a width equal to the electrode sheet and a length 80-200mm longer than the sample is inserted under the electrode sheet and secured with wrinkle adhesive. The power supply of the Sansi tensile testing machine (sensitivity 1N) is turned on; the indicator light illuminates. The limit block is adjusted to a suitable position, and the end of the steel plate without the electrode sheet attached is secured with the lower clamp. The paper strip is folded upwards and secured with the upper clamp. The position of the upper clamp is adjusted using the "up" and "down" buttons on the manual controller attached to the tensile testing machine. The test is then performed, and the values ​​are read. Three tests are conducted, and the average value is taken.

[0220] (8) Tensile strength and elongation at break tests of adhesive film with a thickness of 0.5 mm prepared from adhesive precursor.

[0221] An appropriate amount of adhesive precursor was placed in a polytetrafluoroethylene petri dish and baked in a forced-air drying oven at 105°C for 24 hours to obtain a polymer film with a thickness of 0.5 mm.

[0222] The tensile strength and elongation at break of the polymer film were tested using a tensile testing machine. The film, prepared by drying the adhesive precursor, was clamped in a fixture, a tensile force was applied, and the tensile force was gradually increased until the film was destroyed. The tensile force-displacement curve was recorded, and the tensile strength and elongation at break were calculated.

[0223] (9) Cycle performance test of individual battery cells

[0224] The prepared battery was tested at 25℃ using the testing system of Wuhan Landian Electronics Co., Ltd. It was charged to 4.25V with a constant current of 1 / 3C, then charged to 0.05C with a constant voltage of 4.25V, left to rest for 5 minutes, and then discharged to 2.5V with 1 / 3C. The resulting discharge capacity was recorded as the initial capacity C0. The above steps were repeated for the same battery, and the discharge capacity C of the battery after the 100th cycle was recorded. The battery capacity retention rate after each cycle is P = (C / C0) × 100%.

[0225] The performance test results are shown in Tables 1 and 2.

[0226] Table 1

[0227]

[0228]

[0229] In Table 1, T represents the temperature at which the coated negative electrode sheet is vacuum dried;

[0230] In Examples 1-10, M1 represents the mass fraction of the binder precursor, with the total mass fraction of the binder precursor, conductive agent, and negative electrode active material being 100%.

[0231] Comparative Examples 1-4 did not have binder precursors, and the relevant parameters of the corresponding binder precursors were regarded as their binder parameters. For example, M1 is the mass fraction of the binder in the negative electrode active material layer of Comparative Examples 1-4.

[0232] Table 2

[0233]

[0234]

[0235] In Table 2, similar to Table 1, comparative examples 1 to 4 do not have binder precursors, and the relevant parameters of the corresponding binder precursors are regarded as their binder parameters.

[0236] As can be seen from the data in Tables 1 and 2, the benzene ring and imide structures in the binder precursor of this embodiment exhibit good mechanical strength and tensile strength. The introduction of electron-withdrawing groups into its aromatic ring side chains enhances the interfacial bonding between the binder and silicon particles, strengthens the integrity of silicon during volume expansion, and prevents detachment or pulverization, thereby enhancing the structural stability of the negative electrode active material layer and improving the cycle performance of the battery. Comparative Example 1 uses SBR / CMC binder, Comparative Example 2 uses PAA binder, and Comparative Example 3 uses PVA binder. Their bonding strength, tensile strength, and flexibility are inferior to those of the embodiments, therefore the cycle performance of the battery cells prepared using them is not as good as that of the embodiments. The side chain groups in Comparative Example 4 cannot promote the imidization reaction, resulting in low imidization efficiency during electrode drying and inferior cycle performance compared to the embodiments.

[0237] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limiting the present disclosure, and that changes, substitutions and modifications can be made to the embodiments without departing from the spirit, principles and scope of the present disclosure.

Claims

1. A battery cell, characterized in that, The battery cell includes a negative electrode sheet, the negative electrode sheet includes a current collector and a negative electrode active material layer stacked together, the negative electrode active material layer includes a binder, and the binder includes a compound having the structure shown in formula (I); Each of R1 to R8 independently represents at least one of the following: hydrogen atom, sulfonic acid group, nitro group, cyano group, fluoroalkyl group, carboxyl group, acyl group, formyl group, ester group, and amide group; at least one of R1 to R8 includes one of the following: sulfonic acid group, nitro group, cyano group, fluoroalkyl group, carboxyl group, acyl group, formyl group, ester group, and amide group.

2. The battery cell according to claim 1, characterized in that, Each of R1 and R3 independently includes at least one of sulfonic acid group, fluoroalkyl group, nitro group, and cyano group.

3. The battery cell according to claim 1 or 2, characterized in that, R2 and R4 each independently include at least one of the following: hydrogen atom, sulfonic acid group, nitro group, cyano group, fluoroalkyl group, and carboxyl group.

4. The battery cell according to any one of claims 1 to 3, characterized in that, R5 to R8 are all hydrogen atoms.

5. The battery cell according to any one of claims 1 to 4, characterized in that, R1 and R3 are each independently selected from at least one of sulfonic acid group, fluoroalkyl group, nitro group, and cyano group.

6. The battery cell according to any one of claims 1 to 5, characterized in that, The negative electrode sheet includes a negative electrode active material, which includes one or more of silicon-carbon composite materials, silicon oxide, silicon-nitrogen composite materials, elemental silicon, and silicon alloys; the mass percentage of silicon in the negative electrode active material is 40%-50%.

7. The battery cell according to any one of claims 1 to 6, characterized in that, The negative electrode sheet must satisfy at least one of the following characteristics: (1) The thickness of the negative electrode active material layer is 20 μm to 80 μm; (2) The bonding force of the negative electrode sheet is 100N / m to 500N / m.

8. The battery cell according to any one of claims 1 to 7, characterized in that, The compaction density of the negative electrode active material layer is 0.8 g / cm³. 3 ~1.1g / cm 3 .

9. A battery device, characterized in that, It includes multiple battery cells as described in any one of claims 1 to 8.

10. An electrical appliance, characterized in that, Includes the battery cell as described in any one of claims 1 to 8 or the battery device as described in claim 9.

11. A method for preparing a single battery cell, characterized in that, include: Preparation of negative electrode sheet: A binder precursor as shown in formula (II) is provided. The binder precursor is mixed with a conductive agent and a negative electrode active material in a solution to prepare a negative electrode slurry. The negative electrode slurry is coated on the surface of at least one side of the current collector and dried to obtain a negative electrode sheet. The electrode assembly, including the negative electrode sheet, is assembled into a single battery cell; R1 ’ Up to R8 ’ Each independent representation includes at least one of the following: hydrogen atom, sulfonic acid group, nitro group, cyano group, fluoroalkyl group, carboxyl group, acyl group, formyl group, ester group, and amide group; R1 ’ Up to R8 ’ At least one of the following groups is included: sulfonic acid group, nitro group, cyano group, fluoroalkyl group, carboxyl group, acyl group, formyl group, ester group, and amide group.

12. The method for preparing a battery cell according to claim 11, characterized in that, During the preparation of the negative electrode sheet, the drying temperature is 100℃~140℃.

13. The method for preparing a battery cell according to claim 11 or 12, wherein the weight-average molecular weight of the binder precursor is 50 kDa to 300 kDa.

14. The method for preparing a battery cell according to any one of claims 11 to 13, characterized in that, The adhesive precursor, when prepared into a 0.5 mm thick film, is immersed in a solvent of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a mass ratio of 1:1:1 at 60°C for 24 hours, and the swelling degree is 10% to 30%.

15. The method for preparing a battery cell according to any one of claims 11 to 14, characterized in that, The viscosity of the aqueous solution of the binder precursor with a solid content of 20% is 1500 mPa·s to 3000 mPa·s.

16. The method for preparing a battery cell according to any one of claims 11 to 15, characterized in that, The binder precursor must satisfy at least one of the following characteristics: (1) The adhesive precursor is made into a 0.5 mm thick adhesive film with a tensile strength of 50 MPa to 150 MPa; (2) The elongation at break of the adhesive precursor made into a 0.5 mm thick film is 10% to 30%.

17. The method for preparing a battery cell according to any one of claims 11 to 16, characterized in that, With the total mass fraction of the binder precursor, conductive agent, and negative electrode active material being 100%, the mass fraction of the binder precursor is 1% to 10%.

18. The method for preparing a battery cell according to any one of claims 11 to 17, characterized in that, The binder precursor comprises at least one of the compounds with structures shown in formulas (II-1) to (II-4):